Negotiating Living Hadith in Public Spaces: The Case of Salafi Muslimah Religious Study Groups in Yogyakarta - Marhumah; Iffah Khoiriyatul Muyyassaroh; Rosalia Sciortino (UIN Sunan Kalijaga Yogyakarta, 2025)
This study examines how Salafi Muslimah in Yogyakarta negotiate the implementation of Living Hadith in public spaces, particularly in relation to gender roles. Using a qualitative case study approach, it analyzes interpretations of hadith concerning women's obedience to their husbands, hijab, and religious participation. Data were collected through six months of participant observation and in-depth interviews with twelve informants from four universities, whose identities were anonymized to ensure privacy. Methodological rigor was maintained through triangulation, member checking, and peer debriefing to enhance the study's validity. Data analysis was conducted using thematic coding. The findings indicate that many Salafi Muslimah participants tend to adopt a literal and conservative interpretation of hadith. However, instances of negotiation were also observed, reflecting internal discourse within the community. These results contribute to the broader discourse on how Muslim women engage with religious teachings in their daily lives, particularly within the Salafi movement, which is noted for its strict adherence to traditional religious texts. Despite its significant contributions, this study is limited by its narrow geographical focus and reliance on qualitative methods, which may not fully capture the diversity of interpretations across different Salafi communities. Future research should expand the geographical scope and adopt mixed-method approaches to provide a more comprehensive understanding of this phenomenon.